Analisis Pengelolaan Dana Desa pada Desa Semuntai Kecamatan Mukok Kabupaten Sanggau - Perdana, Ilham Rizki (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This study aims to analyze village fund management in supporting village development and to assess the conformity of village fund management and reporting systems with Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Financial Management. This study employs a descriptive qualitative approach. Primary data were collected through interviews and observations, while secondary data were obtained from documentation and literature studies. The informants included village government officials involved in village financial management, such as the village head, village secretary, heads of administrative affairs, heads of sections, members of the Village Consultative Body, and community representatives. The results indicate that village fund management in Semuntai Village, Mukok District, Sanggau Regency, is categorized as very good because it applies the principles of transparency, accountability, efficiency, and community participation. The conformity assessment shows that 22 of 25 indicators, or 88%, comply with Minister of Home Affairs Regulation Number 20 of 2018. However, three indicators, or 12%, remain noncompliant, particularly in the implementation and financial administration stages.